Effects of inspiratory muscle training on respiratory muscle electromyography and dyspnea during exercise in healthy men - Ramsook, Andrew H. (J Appl Physiol (1985), 2017)
Inspiratory muscle training (IMT) has consistently been shown to reduce exertional dyspnea in health and disease; however, the physiological mechanisms remain poorly understood. A growing body of literature suggests that dyspnea intensity can be explained largely by an awareness of increased neural respiratory drive, as measured indirectly using diaphragmatic electromyography (EMGdi). Accordingly, we sought to determine whether improvements in dyspnea following IMT can be explained by decreases in inspiratory muscle electromyography (EMG) activity. Twenty-five young, healthy, recreationally active men completed a detailed familiarization visit followed by two maximal incremental cycle exercise tests separated by 5 wk of randomly assigned pressure threshold IMT or sham control (SC) training. The IMT group (n = 12) performed 30 inspiratory efforts twice daily against a 30-repetition maximum intensity. The SC group (n = 13) performed a daily bout of 60 inspiratory efforts against 10% maximal inspiratory pressure (MIP), with no weekly adjustments. Dyspnea intensity was measured throughout exercise using the modified 0–10 Borg scale. Sternocleidomastoid and scalene EMG was measured using surface electrodes, whereas EMGdi was measured using a multipair esophageal electrode catheter. IMT significantly improved MIP (pre: −138 ± 45 vs. post: −160 ± 43 cmH(2)O, P < 0.01), whereas the SC intervention did not. Dyspnea was significantly reduced at the highest equivalent work rate (pre: 7.6 ± 2.5 vs. post: 6.8 ± 2.9 Borg units, P < 0.05), but not in the SC group, with no between-group interaction effects. There were no significant differences in respiratory muscle EMG during exercise in either group. Improvements in dyspnea intensity ratings following IMT in healthy humans cannot be explained by changes in the electrical activity of the inspiratory muscles. NEW & NOTEWORTHY Exertional dyspnea intensity is thought to reflect an increased awareness of neural respiratory drive, which is measured indirectly using diaphragmatic electromyography (EMGdi). We examined the effects of inspiratory muscle training (IMT) on dyspnea, EMGdi, and EMG of accessory inspiratory muscles. IMT significantly reduced submaximal dyspnea intensity ratings but did not change EMG of any inspiratory muscles. Improvements in exertional dyspnea following IMT may be the result of nonphysiological factors or physiological adaptations unrelated to neural respiratory drive.